Human Resources Development of Village Apparatus as a Response to the Determination of Betang Long as a Tourism Allegation Areas Based on Cultural Heritage Case study in Ensaid Panjang Village, Kelam Permai District, Sintang Regency, West Kalimantan - Pether Sobian; Gunawan Gunawan; Mikael Mahin; Darmansyah Darmansyah; Yudika Cahyana (Wacana Journal of Social and Humanity Studies, 2022)
The village in Ensaid Panjang Village is located in Sintang Kota, Sintang District. This village has been around for a long time as part of the government agency that handles Ensaid Panjang issues. Ensaid Panjang village has its own building with a total of 14 officers. Ensaid Panjang Village is led by a village head who is responsible for the sub-district head. The village apparatus in Ensaid Panjang Village, Sintang Regency is 14 people consisting of various levels of education and experience. Based on the Decree of the Regent of Sintang No. 362 of 2000 concerning the Establishment of Regional Apparatus Institutions regarding the composition and working procedures of the village, Ensaid Panjang is a supporting element for implementing district government in the field of Ensaid Panjang. This type of research is a qualitative descriptive study. Based on the understanding of descriptive research according to the experts mentioned above, the research that will be carried out by researchers is in the form of descriptive research because it is not a display or narrative of numbers, graphics, or the like. This type of research does not compare, or link one variable to another. Based on the results of the author's observations or observations during the research while the author visited the locus and research site, the author can explain that the organizational structure of the Ensaid Panjang Village government can be seen as the organizational structure. The role of the Village Apparatus in managing the Village Designated Tourism Area is very strategic and important. The village apparatus is one of the village's supporting resources in advancing the village sustainably. Based on the existing human resources of the village apparatus, quite a lot of work is needed to equip, strengthen and improve the capacity of the apparatus in various formal education and training or other forms.